2023
DOI: 10.1039/d3dt00525a
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional polymer nanosheets as a high-performance organic anode for sodium-ion batteries

Abstract: Based on the conjugated system, the sodium 2-amino-4-thiazol-derived polymer (PATANa) exhibits rapid electron/ion transfer kinetics and limited solubility in the electrolyte for significantly enhanced cycling stability and rate capability of SIBs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…For instance, Liao et al demonstrated that the 2,5-dimethoxy-1,4-benzoquinone (DMBQ), an organic cathode material for magnesium batteries, achieved a high initial discharge capacity of 226 mAh g –1 , but due to its dissolution in the electrolyte, the capacity decayed to 74 mAh g –1 after 30 cycles . Currently, several strategies have been proposed to mitigate dissolution, including salification, polymerization, compositing with insoluble materials, , and electrolyte modification . For example, Cui et al employed the addition of LiCl to the all-phenyl complex electrolyte to inhibit the dissolution of 3,4,9,10-perylenetetracarboxylic dianhydride (PTCDA) and improve its cycling stability .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Liao et al demonstrated that the 2,5-dimethoxy-1,4-benzoquinone (DMBQ), an organic cathode material for magnesium batteries, achieved a high initial discharge capacity of 226 mAh g –1 , but due to its dissolution in the electrolyte, the capacity decayed to 74 mAh g –1 after 30 cycles . Currently, several strategies have been proposed to mitigate dissolution, including salification, polymerization, compositing with insoluble materials, , and electrolyte modification . For example, Cui et al employed the addition of LiCl to the all-phenyl complex electrolyte to inhibit the dissolution of 3,4,9,10-perylenetetracarboxylic dianhydride (PTCDA) and improve its cycling stability .…”
Section: Introductionmentioning
confidence: 99%